Assessment of Pharmacological Treatment Quality: Comparison of Symptom-triggered vs. Fixed-schedule Alcohol Withdrawal in Clinical Practice - Müller, U. J.; Schuermann, F.; Dobrowolny, H.; Frodl, T.; Bogerts, B.; Mohr, S.; Steiner, J. (Pharmacopsychiatry, 2016)
Introduction: Despite the fact, that symptom-triggered alcohol withdrawal treatment is recommended by German guidelines on alcoholism, many hospitals continue to use fixed-schedule protocols, as they have been successfully applied for many years.Methods: This retrospective study compared all patients’ records of alcohol withdrawal treatment from October 2010 to November 2011 at Magdeburg’s University Department of Psychiatry (n=120). A symptom-triggered protocol with clomethiazole (AESB, n=46) was used in parallel with the existing fixed-schedule protocol with diazepam (n=74).Results: The symptom-triggered group showed less need of pharmacological treatment duration (p<0.001) and cumulative dosage of medication compared to the fixed-schedule protocol (p<0.006). No difference was observed regarding the need of clonidine or haloperidol (to treat blood pressure derailment or delirium) and the incidence of epileptic seizures.Discussion: Based on the shorter treatment duration and a similar rate of complications our department has switched to the symptom-triggered protocol to improve the quality of patient care.
Keywords: alcohol withdrawal; detoxification; substance dependence disorders